Reducing Online Learning Problem During Covid-19 Pandemic by Utilizing Google Meet - Ni Made Anggi Arlina Putri; Rizqi Akbarani (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2023)
The massive change of learning mode to online platform due to the outbreak of corona virus is the real effect for educational sector all over the world. The online learning is supposed to be promising solution for learning process during the pandemic. However, in developing country such as Indonesia, insufficient of the use of online learning system has also caused many problems encountered by both students and teachers. Choosing the right online learning platform hopping can reduce the barriers during online learning utilization. After eight (8) weeks of only electronic learning, an online survey was conducted to explore the students’ perception on the use of Google Meet in overcoming lecturing problems during the covid-19 pandemic among the Law students. The survey was conducted distributing online questionnaire using Google Form to the second semester of Dharma Sastra’s students. Data gathered from the survey were analyzed using descriptive quantitative method. Twenty-five students answered the online survey and taken as the sample of this study. According to respondents’ answers, most respondents state that the use of Google Meet in online learning is very helpful in overcoming the limitations and obstacles faced during online learning such as the quota burden being lighter because Google Meet does not spend a lot of cost during online learning. Furthermore, respondents also stated that the ease of accessing Google Meet is one factor in the usefulness of this media. Google Meet can be accessed by students using both laptops and cellphones. Another benefit of this Platform is that it is easy to use. Respondents acknowledged that Google Meet is easier to use as a medium for interaction and presentation. So that the quality of online learning is felt to be of higher quality. The results also show that students are still in adjustment in online learning because their perception results are still in the medium category in the usefulness of this platform.